Tactile length-memorisation training for needle depth control: A pilot study of cross-postural skill transfer - Hirohisa Miyachi; Tsunehiko Wada; Miyono Okinaka (Acupuncture in Medicine, 2026)
Objective: The aim of this pilot study was to examine whether tactile length-memorisation training practised in a single basic posture could improve insertion-depth control across different needling postures. Methods: In this single-group pre-post pilot study, eight visually impaired acupuncture students at a school for the blind performed needle insertions to a target depth of 15 mm on a prone practice model before and after a 2-week home-based tactile length-memorisation training programme. Insertions were performed at three sites: posterior (midline of the back), right-lateral (right abdominal region) and left-lateral (left abdominal region). The practitioner’s working posture naturally differed for each site: upright for the posterior, inclined forward and to the right for the right-lateral, and slightly forward for the left-lateral insertion. The training involved repeated tactile memorisation and reproduction of the residual needle length using the fingertips and was conducted only in the basic posture used for needling the posterior region (upright posture). Before and after the training, we computed the mean absolute error, median absolute deviation and the proportion of trials with errors exceeding 5 mm. Outcomes were assessed using paired statistical tests and effect size metrics. Results: The mean absolute error decreased significantly across all regions after training (from approximately 5–6 mm to 1–2 mm). No errors exceeding 5 mm were observed post-training, and median absolute deviation decreased significantly only in the left-lateral region. Conclusion: These preliminary findings suggest that tactile length-memorisation training may enhance insertion-depth precision without visual cues and may be applicable across different needling postures.